Policy options related to roads in tropical forests - Kaimowitz, D. (1999)
Economic theory and empirical evidence suggest that building or improving roads near forests encourage forest clearing for land speculation, agriculture and other activities. Policies used to mitigate the dangers of forest road projects have failed in many countries. Practically all countries now require environmental impact assessments for large road projects near forests but these are often of poor quality and lead to a few protective measures. On the other hand, it is neither feasible nor desirable to prohibit all new road projects near tropical forests as for many rural people who live near forests improving their access to markets and services is among their greatest aspirations and highest priorities. The paper provides a possible set of appropriate policy recommendations related to roads in tropical forests. These are: (1) avoid road construction projects where costs do not justify the economic benefits; (2) include cost recovery provisions in road projects; (3) focus road investments in areas that already have substantial population and/or high quality soils; (4) establish performance bonds for forest concessions which companies will forfeit if farmers encroach on concession lands; (5) respect the territorial rights of indigenous people; and (6) open project documents to public scrutiny.